Identification of races of Bremia lactucae in São Paulo, Brazil - Braz, L. T. [UNESP]; Dalpian, T. [UNESP]; Camargo, M. [UNESP]; Pissardi, M. A. [UNESP] (My University, 2007)
Lettuce, Lactuca sativa, is the most important leafy vegetable in the diet of the Brazilian people. However, the lettuce crop is susceptible to downy mildew disease which is caused by the fungus Bremia lactucae. Downy mildew is most troublesome during winter conditions in regions with mild temperatures. This coincides with the time for growing large quantities of lettuce. The high cost of cultivation and the infection of downy mildew in the winter, just when market prices are low, provides an economic challenge for Brazilian growers. The objective of this study was to identify the races of Bremia lactucae that occur in the growing regions of São Paulo during 2004. The study was conducted in the Laboratory of Vegetable Crop Genetics in the Department of Crop Production of the Faculty of Agricultural and Veterinary Sciences - UNESP, Jaboticabal Campus. In the present study, 92 isolates of B. lactucae were identified from São Paulo. The isolates were shown to display mainly a Sextet code 63/63/51/00 behavior, characterizing the race with regard to coverage and economic importance. The genes that confer resistance accounting for this behavior are DM 17, DM 18 and DM 38. Their use is recommended as sources of resistance to downy mildew in lettuce breeding programs.
Keywords: DM genes; Lactuca sativa; Lettuce downy mildew; Bremia lactucae; Fungi; Lactuca; Peronosporaceae